The origins of intergenerational associations: lessons from Swedish adoption data - Anders Björklund; Mikael Lindahl; Erik Plug (Institute for the Study of Labor (IZA), 2005)
We use unique Swedish data to estimate intergenerational associations between adoptees and their biological and adoptive parents. We argue that the impact from biological parents captures broad pre-birth factors, including genes and prenatal environment, and the impact from adoptive parents represents broad post-birth factors, such as childhood environment, for the intergenerational association in education and income. We find that both pre- and post-birth factors contribute to intergenerational transmissions, and that pre-birth factors are more important for mother's education and less important for father's income. We also find some evidence for a positive interaction effect between post-birth environment and pre-birth factors.
Keywords: I20; J30; J62; 330; intergenerational mobility; nature and nurture; income; education; adoption data; Familienrecht; Kinder; Einkommen; Bildungsniveau; Soziale Mobilität; Schweden; Eltern